MORAL OBLIGATIONS OF COMPUTERS IN DRUG RESEARCH - Sunil Kumar Prajapati, Pushpraj S Gupta, Satendra Singh, Maneesh K Pandey, Pavan Kumar, Ruchi Tiwari (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2023)
To look into the ethics of using computers in pharmaceutical research, as well as the issues that come with it and start by looking at how philosophers think about computer ethics. With regard to computer ethics, the philosophical community is unsure whether or not it is confronted with a whole new topic of study. We identify the issues and areas in which philosophers have shown the most interest with regard to computer ethics, namely, the questions of privacy, liability, ownership, and power, after addressing the issue of how to treat computer ethics in terms of its philosophical classification.